OPTIMIZING REGIONAL ASSET MANAGEMENT THROUGH RISK-BASED ACCOUNTING STRATEGIES: BOMBANA REGENCY PUBLIC WORKS AND SPATIAL PLANNING DEPARTMENT - Muhamad Rahman Al Akbar; Mohammad Jihadi; Rizki Febriani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the optimization of regional asset management through a risk-based accounting strategy at the Public Works and Spatial Planning (PUPR) Office of Bombana Regency. The background of the study stems from common problems in regional asset management such as inconsistencies in recording, suboptimal utilization, and weak internal control systems, which are often audit findings. The risk-based accounting approach becomes relevant following the issuance of the Minister of PUPR Circular Letter No. 12/SE/M/2024 concerning guidelines for implementing risk management, which emphasizes the integration of corruption, legal, SPBE, and service risks into organizational governance. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews, observation, and documentation studies. The results show that asset management at the PUPR Office of Bombana is still administratively oriented and has not fully implemented risk management principles in asset planning, recording, utilization, and maintenance. However, awareness of the importance of risk-based management is starting to grow through internal policies and improvements to the information system. In conclusion, the implementation of a risk-based accounting strategy has the potential to increase accountability, efficiency, and the economic value of regional assets if supported by an integrated information system and adequate human resource capacity.